(untitled) (Research, Society and Development, 2021)
This work aims to analyze, casting a problematic look at the issues that have marked the performance of a teacher with a kindergarten II class, starting from the narratives of her students, their feelings and actions that are frequently present and that characterize the concepts they present about the relationship between being a teacher and being young and the refusal to accept as teachers people who do not fit within the concepts of beauty and youth established by them. These questions propelled the need to investigate and accurately analyze the personal and family issues that govern the behavior of these children, using studies that are characterized as post-structuralist as a research reference, especially the studies by Foucault. This age discrimination presented by the students, provided too many results that encompass subjectivity, as well as the effect of the beauty empire.